2015
DOI: 10.1051/0004-6361/201526184
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the dust trail of 67P/Churyumov-Gerasimenko: an application of the IMEX model

Abstract: Context. Here we describe a new model of the dust streams of comet 67P/Churyumov-Gerasimenko that has been developed using the Interplanetary Meteoroid Environment for Exploration (IMEX). This is a new universal model for recently created cometary meteoroid streams in the inner solar system. Aims. The model can be used to investigate characteristics of cometary trails: here we describe the model and apply it to the trail of comet 67P/Churyumov-Gerasimenko to develop our understanding of the trail and assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 35 publications
(64 reference statements)
3
49
0
Order By: Relevance
“…This is in agreement with the findings of Snodgrass et al (2013) for the previous orbit and their predictions for the current orbit. In their trail model, Soja et al (2015) reported values of ∼10 kg s −1 at 3 au, which is in line with ours, but of ∼3.5 kg s −1 at 4.3 au, a value that is considerably larger than our estimate at that heliocentric distance.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This is in agreement with the findings of Snodgrass et al (2013) for the previous orbit and their predictions for the current orbit. In their trail model, Soja et al (2015) reported values of ∼10 kg s −1 at 3 au, which is in line with ours, but of ∼3.5 kg s −1 at 4.3 au, a value that is considerably larger than our estimate at that heliocentric distance.…”
Section: Resultssupporting
confidence: 91%
“…Thus, the particle differen-tial size distribution was found to be adequately described by a differential power law of index α=-2, except for the largest particle size bins (r 1 mm) for which an index α=-4 is needed to satisfy the 67P trail data, which are mostly sensitive to those large particles, and which were acquired in previous revolutions . A close value of α ∼-3.7 for large particles has been found by Soja et al (2015) from analysis of 67P trail Spitzer data. This also agrees with the distribution of blocks that are larger than a few centimetres in size on the surface of smooth terrains found by Mottola et al (2015) (α=-3.8±0.2) from the Rosetta Lander Imaging System (ROLIS) on board Philae.…”
Section: Introductionsupporting
confidence: 77%
“…The initial particle orbits were integrated for 1 Myr using the "PIntegrator", which uses a Runge-Kutta-Nyström 7(6) method with variable step size (Dormand & Prince 1978) to propagate the trajectories of all dust particles under solar and planetary gravity; radiation pressure; and Poynting-Robertson drag force, with a factor also included for solar wind drag (Soja et al 2015). Particles that came within ten solar radii of the Sun were removed to manage the integration process and because particles inward of this distance are expected to sublimate (Mann et al 2011).…”
Section: Modelling the Long-term Trajectories Of Cometary And Asteroimentioning
confidence: 99%
“…Recently, the Interplanetary Meteoroid Environment for eXploration (IMEX) dust streams in space model was developed by Soja et al (2015bSoja et al ( ,a, 2019 under contract by the European Space Agency. IMEX is a new universal and physical model for dust dynamics and orbital evolution that simulates recently created cometary dust trails in the inner Solar System.…”
Section: Introductionmentioning
confidence: 99%